The Effectiveness of Ethanol Extract of Neem Leaf (Azadirachta indica) Mouthwash Against The Growth of Streptococcus sp. - Muhammad Abdurrahman; Endang Sri Lestari; Tyas Prihatiningsih (Faculty of Medicine, Universitas Diponegoro, 2022)
Background: Streptococcus sp. is a bacteria group in the oral cavity that plays a significant role in initiating plaque biofilm formation on teeth. One way to control plaque is gargling with mouthwash. Neem leaves contain antibacterial compounds such as alkaloids, steroids, glycosides, and flavonoids that can be formulated as mouthwash ingredients.Objective: The study aimed to determine the effectiveness of Ethanol Extract of Neem Leaf (EENL) mouthwash on the growth of Streptococcus sp.Methods: The research design was a pretest-posttest control group. The 28 samples of Streptococcus sp. were divided into 7 treatment groups (4 repetitions). The treatment group was given EENL mouthwash with concentrations of 2.5%, 5%, 7.5%, 10%, and 12.5%, a negative control was given aquadest and positive control was given 0.2% chlorhexidine gluconate. Bacterial growth is known through the absorbance values. Data analysis used one-way Anova test and post hoc LSD test at p<0.05Results: EENL mouthwash has antibacterial activity against Streptococcus sp. One way ANOVA test on the difference in absorbance values shows a p=0.00. LSD post hoc test between EENL concentration of 2.5% and chlorhexidine 0.2% showed equivalent antibacterial activity (p>0.05). Meanwhile, the post hoc LSD test between concentrations of 5% - 12.5% with 0.2% chlorhexidine showed a significant difference in antibacterial power (p<0.05). This indicates a stronger antibacterial activity at a concentration of 5% - 12.5% compared to 0.2% chlorhexidine.Conclusion: EENL mouthwash effective against the growth of Streptococcus sp